Photocatalytic activity of WO3/Fe2O3 nanocomposite photoanode. (27th July 2015) - Memar, Amir; Phan, Chi M.; Tade, Moses O.
Abstract: The (WO3 )1−x –(Fe2 O3 )x (0 ≤  x  ≤ 1) nano-particle thin films with various compositions have been deposited onto the fluorine thin oxide (FTO) coated glass substrate using sol-gel, spin-coating technique. An electrode/electrolyte interface has been formed between an n-type (WO3 )1−x –(Fe2 O3 )x composite semiconductor and a 0.5 mol L −1 Na2 SO4 aqueous solution. The photo-catalytic activity of the films has been investigated through the photocurrent-voltage. UV-visible spectroscopy, SEM and XRD have been used to characterize solar absorption, surface morphology and the crystallinity of samples, respectively. The photo-electrochemical (PEC) experiments were performed under solar irradiation to evaluate the amount of electron-hole generation in different samples. All the composite nano-particles indicated higher efficiency compared to pristine iron and tungsten oxides. A clear relationship was also confirmed between band gap energy and photo-catalytic activity of thin films. The band-gap energy of mixed thin films decreased linearly with the increasing Fe2 O3 content in the film samples. The maximum photocurrent density of 2.34 mA cm −2  has been obtained for sample with x  = 0.25 at 1.4 V vs. RHE. The result revealed that the sample also has the highest photon-to-current efficiency (0.87%), and solar absorption. Highlights: Nanocomposite WO3 /Fe2 O3 materials have successfully been synthesized. The morphology of nanocomposites were distinguishingly altered. The nanocomposites exhibited higher activity compare to pristine WO3 and Fe2 O3 . (WO3 )0.75 –(Fe2 O3 )0.25 revealed the highest photocatalytic activity.